2022
DOI: 10.1007/s00296-022-05240-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in perceived expectations of the outcome of total hip and knee arthroplasties and their fulfillment: an observational cohort study

Abstract: The influence of sex on preoperative expectations and their fulfillment following total hip and knee arthroplasty (THA/TKA) remains unexplored. We investigated differences between men and women in perceived preoperative expectations on the outcome of THA/TKA and their fulfillment 1 year postoperatively. We performed a cohort study. Expectations were collected preoperatively and 1 year postoperatively using the Hospital for Special Surgery Hip/Knee Replacement Expectations Surveys (HSS-HRES/KRES; not applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Although an emerging topic of research, the concordance of demographic characteristics between health-care providers and patients may have numerous benefits that lead to more equitable access to health care among underrepresented groups. Furthermore, unique considerations exist for female patients, including different patient expectations, complications, and surgical outcomes following total joint arthroplasty surgery 19-24 . Considering that trial findings are disseminated into clinical care guidelines and protocols, adequate sex diversity of clinical trial participants ensures that these findings apply equally to men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an emerging topic of research, the concordance of demographic characteristics between health-care providers and patients may have numerous benefits that lead to more equitable access to health care among underrepresented groups. Furthermore, unique considerations exist for female patients, including different patient expectations, complications, and surgical outcomes following total joint arthroplasty surgery 19-24 . Considering that trial findings are disseminated into clinical care guidelines and protocols, adequate sex diversity of clinical trial participants ensures that these findings apply equally to men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate planning and guidance are needed to advise women before surgery regarding different expectations and a potentially unique set of complications following hip and knee arthroplasty. Research has shown that, compared with men, women have worse postoperative outcomes following hip and knee arthroplasty, such as higher rates of infection and venous thromboembolism and lower patient satisfaction 21-27 . Sex discordance between surgeons and patients can lead to worse surgical outcomes, including increased complications and even death 12 .…”
Section: Discussionmentioning
confidence: 99%
“…As walking itself may counteract functional decline (6)(7)(8)(9), low walking activity could lead to further worsening of gait capacity in individuals with knee OA. Given this apparent vicious circle between limitations in gait capacity and walking activity, mitigating walking limitations is of great importance to individuals with knee OA (10) and constitutes a reason to consider total knee arthroplasty (TKA) (11,12). Insights about the extent of walking limitation is therefore relevant for individuals with knee OA opting for TKA.…”
Section: Introductionmentioning
confidence: 99%